Conflicts in a transnational world - "Langenohl, Andreas(ed.)" (New York, 2006)
This volume brings together views on the nexus and the conflicts between transformation of states and societies and transnationalization processes in politics, economy, and culture. Thematic articles and case studies deal with conditioned nations/states in Latin America, Eastern Europe, and the former Soviet Union. These nations/states are, on the one hand, subjected to transnational institutions, models, and forces and cannot fall back on the model of the classic nation state. On the other hand, the issues traditionally linked to the nation state as a polity - sovereignty, national economy, and identity - are still salient, as they serve to describe and evaluate the consequences of transnationalization. The volume addresses those processes as imminently political ones and poses the question of a transnational polity.
Keywords: Conflicts-National sovereignty